CLIENT-SIDE WEB MAPPING SYSTEM FOR VINEYARD SUITABILITY ASSESSMENT - N. Iwasaki; K. Hayashi; T. Tanaka; M. Katori; A. Onohara; T. Oguchi (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2022)
Currently, several types of geospatial data are provided as open data and/or map tile data. This implies that geospatial data have become more barrier-free than older data with traditional licenses and formats. In this study, we used open geospatial data to develop a client-side web mapping system for assessment of site suitability for vineyards. As the research area for testing the system, we selected Nagano Prefecture, where many farmers recently started viticulture. The data used in the system are geology, soil, slope gradient, slope aspect, annual mean temperature, and annual maximum and minimum temperatures. These data were converted to a Grid PNG tile, which was developed by The Geological Survey of Japan, National Institute of Advanced Industrial Science and Technology. FOSS4G tools, such as QGIS, TileMill, and MBUtil were used to prepare Grid PNG tile data. Map algebra functions were implemented using the WebGL. Web mapping systems developed in this research do not require server-side systems and/or middleware and can be operated using only a web browser. This means that various entities can be operated on the same system at low cost, or on a free web service such as GitHub pages.